Anesthesia and perioperative management of colorectal surgical patients - A clinical review (Part 1) - Santosh Patel; Jan M Lutz; Umakanth Panchagnula; Sujesh Bansal (Wolters Kluwer Medknow Publications, 2012)
Colorectal surgery is commonly performed for colorectal cancer and other pathology such as diverticular and inflammatory bowel disease. Despite significant advances, such as laparoscopic techniques and multidisciplinary recovery programs, morbidity and mortality remain high and vary among surgical centers. The use of scoring systems and assessment of functional capacity may help in identifying high-risk patients and predicting complications. An understanding of perioperative factors affecting colon blood flow and oxygenation, suppression of stress response, optimal fluid therapy, and multimodal pain management are essential. These fundamental principles are more important than any specific choice of anesthetic agents. Anesthesiologists can significantly contribute to enhance recovery and improve the quality of perioperative care.